Workload Analysis for Employees with Multiple Positions - Riza Umamah; Roziana Ainul Hidayati (Universitas Muhammadiyah Gresik, 2024)
Several divisions in the organizational structure of PT. Gresik Cipta Sejahtera has a number of employees who play multiple roles (dual positions) which occurs due to vacancies in formation but there must be employees to fill these vacancies. Employees who hold concurrent positions are appointed by letter of appointment or decision letter. Employees who hold multiple positions receive excessive workloads and need additional time to complete their tasks. These additional tasks can increase the employee's workload. The purpose of this research is to determine the workload of employees who hold concurrent positions at PT. Gresik Cipta Sejahtera. The method used in this research is qualitative. The informants in this research were employees who held concurrent positions and also their managers, totaling 5 people. Based on the results of the research and discussion regarding the workload of employees who hold double positions, the researchers came to the conclusion that employees who hold double positions have to work overtime to complete the work.